MODIFIKASI TEPUNG GANYONG (Canna edulis Kerr.) METODE HEAT MOISTURE TREATMENT PADA SUHU DAN WAKTU PEMANASAN BERBEDA DAN APLIKASI TEPUNG PADA PEMBUATAN COOKIES - yudi garnida (Pasundan Food Technology Journal (PFTJ), 2019)
The purpose of this study was to determine the effect of modification of flour ganyong with temperature variations and heating time can improve the characteristics of flour ganyong and increase its use in food processing. The experimental design used in this study is a 3 x 3 factorial pattern in Randomized Block Design (RBD) and replication conducted three times, resulting in 27 experimental units. Factors used in the study were Heat Moisture Treatment (HMT) heating temperature (80°C, 90°C and 100°C) and Heat Moisture Treatment (HMT) heating time (1 hour, 2 hours and 3 hours). The main research responses include chemical responses: pasting properties, moisture content, amylose content and crude fiber content. Based on the result of the research, Heat Moisture Treatment (HMT) heating temperature has an effect on pasting properties, moisture content, amylose content and crude fiber content. Heat Moisture Treatment (HMT) heating time has an effect on pasting properties, moisture content, amylose content and crude fiber content. The interaction between temperature and heating modification time of Heat Moisture Treatment (HMT) has an effect on pasting properties, moisture content, amylose content and crude fiber content. The result of this research is the sample of m3n3 (heating temperature 100°C and heating time 3 hours) with average water content 5,47%, amylose 27,07% and viscosity setback 856,7 Cp. The preparation of cookies from selected modified ganyong flour is carried out by the organoleptic response test. Based on the test results of ganyong flour cookies modification Heat Moisture Treatment (HMT) is preferred in terms of taste, color and texture.